Comparative evaluation of enzyme-linked immunosorbent assay based on crude and purified antigen in the diagnosis of canine visceral leishmaniasis in symptomatic and oligosymptomatic dogs - Candido, Teresinha Cristina [UNESP]; Venturoli Perri, Silvia Helena [UNESP]; Gerzoschkwitz, Tatiana de Oliveira; Luvizotto, Maria Cecília Rui [UNESP]; Felix de Lima, Valeria Marcal [UNESP] (Elsevier B.V., 2008)
This study evaluated the performance of crude total antigen (CTA) and fucose-mannose ligand antigen (FML) in an enzyme-linked immunosorbent assay for diagnosis of canine visceral leishmaniasis (CVL). The assays used sera from known negative controls (n = 30), clinically symptomatic (n = 30) and oligosymptomatic (n = 30) parasitologically proven infection (by microscopy). Aspirates of popliteal lymph node from infected canines were colleted to score parasitism and compared with the ELISA results. The study indicated that FML used in ELISA provided high sensitivity for detecting oligosymptomatic dogs (90%) and CTA showed greater sensitivity than FML for symptomatic canines (90%). In oligosymptomatic dogs, specificity was 100% for CTA-ELISA, but in symptomatic dogs, FML specificity was higher (96.7%) than CTA-ELISA (93.3%). A significant correlation was observed between the degree of parasitism and the results obtained in CTA-ELISA. Since no available antigen offers 100% specificity and sensitivity for CVL diagnosis, the choice of antigen used must depend on the aim of the investigation. (C) 2008 Elsevier B.V. All rights reserved.
Keywords: Dog; Visceral leishmaniasis; ELISA; Fucose-mannose ligand